DIAGNOSIS AND TREATMENT OF PERIODONTAL DISEASE IN PREGNANT WOMEN - Островська, Л.Й. (World of Medicine and Biology, 2015)
The early diagnosis of dental diseases and the effectiveness of their prevention during pregnancy, as well as the correct tactics of the dentists and obstetricians are the determining factors of improving the dental health of pregnant women. The importance of an individualized approach to preventive and curative interventions is particularly important during pregnancy because their effectiveness determines not only the high level of women's health, including dental, but also prevents of numerous pathological conditions and diseases of the unborn child.
Keywords: periodontal disease; pregnant women; diagnostics; treatment